Dr. Ernesto Galarza Scholarship Symposium Program 1994 - Chicano/Latino Faculty and Staff Association::::::::::::::: (2024)
Program for the 10th Annual Dr. Ernesto Galarza Scholarship Symposium, held at San Jose State University on Thursday, April 21, 1994 at 5:30 PM – 8:30 PM. This event included a Social Hour, Welcome by Dr. Lou Holscher (Vice President, Chicano/Latino Faculty and Staff Association) and Dr. Maynard Robinson (Academic Vice President), Introduction of Keynote Speaker by Mr. Gabe Reyes (President, CLFSA), Keynote Presentation by Ms. Sofia Mendoza (Community Activist), and Presentation of Scholarships by Ms. Deanna Gonzales. Ten awards were presented: Chicano/Latino Faculty and Staff Association Scholarship, Ernesto Galarza Scholarship, Cesar Chavez Memorial Scholarship, Latino Pride Scholarship (2 awards), Mexican American Community Services Association (MACSA) Scholarship (2 awards), Pueblo de San José Kiwanis Scholarship (2 awards), and Nu Alpha Kappa Scholarship.